Login
Remember
Register
Home
All Activity
Q&A
Questions
Hot!
Unanswered
Tags
Categories
Users
Ask a Question
Ask a Question
`8x – 7 – 3x = 6x – 2x –
0
votes
asked
Jan 18, 2022
in
8th-maths
by
krutika
(
1.7k
points)
`8x – 7 – 3x = 6x – 2x – 3`
marks2
chapter4
#sub
Please
log in
or
register
to answer this question.
0
Answers
Categories
All categories
Maths
(8.6k)
12th-maths
(0)
11th-maths
(0)
10th maths
(0)
9th-maths
(0)
8th-maths
(8.6k)
Science
(14)
Physics
(3.4k)
Related questions
`3 (5x – 7) + 2(9x – 11) = 4(8x – 7) –
The value of x for which the expressions 3x – 4 and 2x + 1 become equal
Solve `5x – 2 (2x – 7) = 2 (3x – 1) +
Solve `5x – 2 (2x – 7) = 2 (3x – 1) +
Solve `5x – 2 (2x – 7) = 2 (3x – 1) +